The Effect of Facilities and Locations on the Decision to Visit Resinda Sport Club Karawang: marketing Management - Rendy Fajar Sanusi; Odang Kusmayadi (Fakultas Bisnis, 2022)
The purpose of this study was to determine the effect of facilities and location on the decision to visit the resinda sport club karawang. The method used in this research is verification with a quantitative approach. The samples used were 376 samples. The sampling technique used in this study is a simple random sampling technique , because all related populations have the opportunity and opportunity to be selected as samples. The result of this research is that there is a correlation between facilities and location which has a positive correlation of 0.712 or in the strong category. Partial Effect of Facilities on Visiting Decisions produces a value of 0.295 or 29.5%. Partial Effect of Location on Visiting Decisions produces a value of 0.292 or 29.2%. Simultaneous influence of Facilities and Locations on Visiting Decisions resulted in a value of 0.587 or 58.7%, while the remaining 41.3% were other variables not examined in this study .